A testemunha às avessas ou o narrador desconfiado: história e ficção em Memórias do Cárcere - Santos, Fábio José dos (2013)
By considering Memórias do Cárcere a work in which Graciliano Ramos narrates real events occurred in his life, Brazilian literary criticism has focused this work as a document of history, leaving aside its compositional aspects. Therefore, the fictional nature of this narrative is silenced by the critics or just mentioned with no further investigation. The fictional nature of Memórias do Cárcere is most commonly associated to the presence of imaginary aspect, or, it is taken by the stylistic framework that comes close to the literary writing. The aim of this research is to provide an investigation on the presence of fictionality in Graciliano's Memórias do Cárcere, focusing on the search of the locus of the work's compositional process in which the fictional nature is revealed. Hence, it is emphasized the narrator's role as a narrative instance which promotes a reflection on memorialistic literature. We concentrate our attention to examine the narrator as the agent who starts the reflection on the writing process of the text. This study brings into discussion formulations on memory, history and fiction, theorized by Paul Ricour; Hayden White's theoretical assumptions on historical construction. Itis also applied the concepts of “Autobiographical Pact” and “simulation Act” pointed out by Phillipe Lejeune and Wolfgang Iser, respectively. We argue that, by maintaining Graciliano's reasoning tradition on the writing process, it is proposed a literary-memorial continuumin the present work, by associating history and fiction as two complementary discursive fields.